Morbidity attended by postgraduate doctors in Familial and Community Medicine at the first level of assistance. Chimborazo, Ecuador - Liana Elisa Rodríguez Vargas (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: Postgraduate in Familial and Community Medicine involves providing medical attention at first level of assistance units. In it an a complete and reliable information is required about morbidity since it is the condition which generates more demand. Objective: to characterize the attention to the morbidity by postgraduate doctors in Familial and Community Medicine at the first level of assistance. Methods: a descriptive was developed in the population attended due to morbidity by the 29 postgraduate doctors in Familial and Community Medicine at the first level of assistance, during 2015 at Chimborazo, Ecuador. The data were taken from daily registration of consultations and outpatient attention. The variable age, sex and causes of morbidity were analyzed. Results: Patients attended due to acute respiratory infectious diseases (32,2 %). The female group required more attention (63,6 %), adults from 20 to 64 years old (45,2 %) and children under10 years old (33,4 %). Acute respiratory infection was the most frequent cause in children, adolescents and adults and arterial hypertension in older adults. Conclusion: The morbidity attended by the doctors who majored in Familial and Community Medicine at the first level of assistance is characterized by the predominance of acute respiratory infections in children under 10 years old, adolescents and adults from 20 to 64, and arterial hypertension in older adults.